Atividades para aprendizagem do conceito matemático de função - Guimarães, Rita Santos (Universidade Federal de São Carlos, 2010)
The choice of the mathematical content of this work came from the identification of the difficulties of students in High School 1st year with the theme functions through the experiences of this researcher in her teaching practices. In order to facilitate the teaching and learning of the mathematical concept of function, some proposed activities mixed scripts and problems, to use the concept of spontaneous relationship as the basis for the construction of the scientific concept of function. The activities also have the language necessary for basic scientific understanding of the concept that we use to situations of perceived patterns for students to build functions represented by formulas. We explored the transition from discrete to continuous and covered some graphical situations for functions. The activities were settled in small groups of students from two schools in the first year of High School, one public and thr other on a cooperative style. Applications took a week in each school. All data collected were analyzed and compared with the previous observations, following Didactic Engineering as research methodology. So we could reformulate some parts of the sheets of activities to obtain more positive results of its application. We found that these dynamics in general stimulated and encouraged the participation of students in their own learning process. As it was not possible to follow any longer the same class, this prevented us from obtaining more precise information on the effects of the activites. Anyway, we believe that the produced material produced can help other professionals, even if they have to suffer minor changes to be compatible with each situation.
Keywords: Matemática - estudo e ensino; Funções; Resolução de problemas; Estudantes - atividades; Material didático - matemática; Ensino através de problemas; Folhas de atividades; Relation; Function; Teaching through problems; Activity sheets; CIENCIAS EXATAS E DA TERRA::MATEMATICA